2017
DOI: 10.1590/0103-8478cr20160546
|View full text |Cite
|
Sign up to set email alerts
|

Uniformity microsprinkler irrigation system using statistical quality control

Abstract: The objective of this study was to evaluate the use of statistical quality control tools in the analysis of the uniformity of a microsprinkler irrigation system. For the analysis of irrigation Christiansen uniformity coefficient (CUC) and the distribution uniformity coefficient (DU) were statistically analyzed by means of the Shewhart control charts and process capability index (Cp). For the experiment 25 tests were carried out with a single micro sprinkler and subsequently seven different spacing between micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
1
4
0
1
Order By: Relevance
“…Silva et al (2015) by studying the process capability index in saline water self-compensating emitters and also obtained Cpk > Cp. The results also corroborate with Andrade et al (2017) who observed an increase in the process capacity index directly proportional to the mean values of UC and UD.…”
Section: Discussionsupporting
confidence: 90%
“…Silva et al (2015) by studying the process capability index in saline water self-compensating emitters and also obtained Cpk > Cp. The results also corroborate with Andrade et al (2017) who observed an increase in the process capacity index directly proportional to the mean values of UC and UD.…”
Section: Discussionsupporting
confidence: 90%
“…It was observed that the hydraulic head classified as regular in terms of uniformity (10 and 11 kPa), presented points outside the control limits, indicating points outside of the statistical control process, whereas the 12 and 15 kPa hydraulic heads, whose uniformity was classified as good, were under statistical control, with no trend or no point was outside the control limits. In the study by Andrade et al (2017b), although most processes were simple, they were classified as controlled by the Shewhart control chart and considered significant for the evaluation of irrigation. The 10 kPa hydraulic head presented an isolated point outside the control lines, which can be caused by factors such as low pressure (Saraiva et al, 2014), clogging of drippers, energy fluctuations, pressure variations, and climatic factors (Justi and Saizaki, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…A uniformidade é influenciada pelas diferenças de pressão, desgaste do sistema e entupimento, principalmente quando utilizados fertilizantes. Fatores como o espaçamento entre os emissores/aspersores e fatores externos, como o clima e a topografia, além das variações de fabricação também afetam a uniformidade (ANDRADE et al, 2017).…”
Section: Fundamentação Teóricaunclassified